EFEKTIVITAS IMPLEMENTASI PERATURAN MAHKAMAH AGUNG TENTANG RESTITUSI DALAM KASUS TINDAK PIDANA PERDAGANGAN ORANG DI KOTA SAMARINDA - Nafis, Nyzar Ainun; Syarifuddin, La; Alfian, Alfian (Jurnal Ilmiah Advokasi, 2025)
Human trafficking is a violation of human rights that requires state protection, one of which is through the provision of restitution to victims. The Supreme Court Regulation (PERMA) Number 1 of 2022 regulates the restitution mechanism; however, in Samarinda, no victims have yet submitted such claims. This study aims to examine the implementation of PERMA 1/2022 and analyze the obstacles that hinder victims from exercising their right to restitution. Using a socio-legal approach supported by literature review, the research involves law enforcement officers, the Witness and Victim Protection Agency (LPSK), and social institutions as its primary subjects. The findings show that the implementation of PERMA in Samarinda has not been optimal. The main obstacles include weak communication between law enforcement officers and victims, limited outreach, and victims’ lack of understanding of their right to restitution. Academically, this research contributes by highlighting gaps in the restitution mechanism and offering policy recommendations for strengthening institutional coordination, enhancing victim protection, and improving the effectiveness of restitution implementation in Indonesia.Keywords: Implementation; Human Trafficking; Restitution; LPSK; Law Enforcement